2007
DOI: 10.1038/nm1641
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol is an endogenous SERM that inhibits the cardiovascular effects of estrogen

Abstract: The cardioprotective effects of estrogen are mediated by receptors expressed in vascular cells. Here we show that 27-hydroxycholesterol (27HC), an abundant cholesterol metabolite that is elevated with hypercholesterolemia and found in atherosclerotic lesions, is a competitive antagonist of estrogen receptor action in the vasculature. 27HC inhibited both the transcription-mediated and the non-transcription-mediated estrogen-dependent production of nitric oxide by vascular cells, resulting in reduced estrogen-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
349
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(361 citation statements)
references
References 46 publications
7
349
1
4
Order By: Relevance
“…Our study specifically excluded women with prior CHD, yet we still observed an interaction between hormone therapy and baseline cholesterol levels for CHD risk even after adjusting for age. Recently, the cholesterol metabolite, 27-hydroxycholesterol, has been shown to compete with estrogen for binding to vascular estrogen receptors, blocking the beneficial effects of estrogen (nitric oxide production and endothelial cell migration) on murine vascular cells 11 . This study by Umetani et al suggests an attractive and testable hypothesis: that postmenopausal women with a poor lipid profile have elevated levels of 27-hydroxycholesterol, which disables a potential vascular benefit of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Our study specifically excluded women with prior CHD, yet we still observed an interaction between hormone therapy and baseline cholesterol levels for CHD risk even after adjusting for age. Recently, the cholesterol metabolite, 27-hydroxycholesterol, has been shown to compete with estrogen for binding to vascular estrogen receptors, blocking the beneficial effects of estrogen (nitric oxide production and endothelial cell migration) on murine vascular cells 11 . This study by Umetani et al suggests an attractive and testable hypothesis: that postmenopausal women with a poor lipid profile have elevated levels of 27-hydroxycholesterol, which disables a potential vascular benefit of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Umetani et al [40] reported that several hydroxylated cholesterols including 27-hydroxycholesterol [27-OH-C], 22R-OH-C, 24S-OH-C and 25-OH-C bound human ER and human ER . 27-OH-C was the most potent, and in some mammalian cells 27-OH-C functions as a partial agonist for human ER and ER [40][41][42][43].…”
Section: Was the Ancestral Estrogen A Cholesterol Analog?mentioning
confidence: 99%
“…Recently, Umetani et al [40] reported that several hydroxylated cholesterols including 27-hydroxycholesterol [27-OH-C], 22R-OH-C, 24S-OH-C and 25-OH-C bound human ER and human ER . 27-OH-C was the most potent, and in some mammalian cells 27-OH-C functions as a partial agonist for human ER and ER [40][41][42][43]. The Kd of 27-OH-C for ER and ER is about 1.3 M and 0.4 M, respectively [40][41][42], which is over 10 3 times higher than the Kd of E2 for human ER and ER [30,40].…”
Section: Was the Ancestral Estrogen A Cholesterol Analog?mentioning
confidence: 99%
See 2 more Smart Citations